If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + -6)(4x + 9) = 0 Reorder the terms: (-6 + 6x)(4x + 9) = 0 Reorder the terms: (-6 + 6x)(9 + 4x) = 0 Multiply (-6 + 6x) * (9 + 4x) (-6(9 + 4x) + 6x * (9 + 4x)) = 0 ((9 * -6 + 4x * -6) + 6x * (9 + 4x)) = 0 ((-54 + -24x) + 6x * (9 + 4x)) = 0 (-54 + -24x + (9 * 6x + 4x * 6x)) = 0 (-54 + -24x + (54x + 24x2)) = 0 Combine like terms: -24x + 54x = 30x (-54 + 30x + 24x2) = 0 Solving -54 + 30x + 24x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '6'. 6(-9 + 5x + 4x2) = 0 Factor a trinomial. 6((-9 + -4x)(1 + -1x)) = 0 Ignore the factor 6.Subproblem 1
Set the factor '(-9 + -4x)' equal to zero and attempt to solve: Simplifying -9 + -4x = 0 Solving -9 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + -4x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -4x = 0 + 9 -4x = 0 + 9 Combine like terms: 0 + 9 = 9 -4x = 9 Divide each side by '-4'. x = -2.25 Simplifying x = -2.25Subproblem 2
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Solution
x = {-2.25, 1}
| -6r+5s+2t=-11 | | 3(x)=8.25 | | 3x^2-6x+4y^2-13=0 | | 12(y+2)=36 | | 8(x)=8.25 | | 8x+7=127 | | 170+0.25x=375 | | 7200=(756)R(2.5) | | x-8.6=4.1 | | y+5x=-10 | | -2/3+x=22/3 | | 5665*x=100000 | | 6z+17=-7 | | 12d-7+3d=19+14d | | 49x^2-10=0 | | x-.07=139500 | | -2(x-1)-4=-4(1+x)+2x+2 | | x+100=299 | | 2x-3(2x+4)=-6x+10 | | r+34=21 | | 3y+5(-3)y-3=27 | | 4u-w=u-5w | | 79/7=x-5/7 | | 420+d=-196 | | 24m+85=685 | | 2(v-5)-4=-5(-4v+1)-6v | | n+25=24 | | -2x-5y=-11 | | 5x=11x-4 | | 1-6(2-x)-29x=x | | 4u-2=-22 | | -9x+y=71 |